Strategi Kenaikan SHU Melalui Diversifikasi Usaha Koperasi - Fatimah Az Zahrah; Novika Dimyati; Adi Wiratno (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In a dynamic and complex economic context, cooperatives play an important role in supporting local economic development and community welfare. Cooperatives are responsible for ensuring business sustainability and meeting the needs of their members. One relevant and popular strategy to achieve this goal is business diversification. Cooperative business diversification aims to reduce the risk of dependence on one type of business, improve financial stability, and expand sources of income. This research focuses on analyzing the increase in profit surplus (SHU) through cooperative business diversification, using qualitative methods and case studies. Through in-depth interviews, observations, and document analysis, this study identified factors that influence the success of cooperative business diversification. The case study of Koperasi SACIKA shows that the role of organization and management is crucial in designing and implementing business diversification. The results revealed that business diversification has significantly increased the cooperative's SHU, with an example of an increase in profit from IDR 261,364,970 in 2021 to IDR 500,622,533 in 2023. Prudent cost management and active involvement of members in the Annual Members' Meeting (RAT) contributed to the success of the diversification strategy. This research provides valuable insights for cooperative managers and stakeholders on the importance of business diversification in improving the financial well-being of cooperatives. The findings are expected to support the development of more effective and sustainable strategies for cooperative management in the future. This study concludes that business diversification is an important strategic step to face the challenges of the modern economy and improve the welfare of cooperative members.